Optimal regeneration and repair of critical size articular cartilage driven by endogenous CLECSF1. (September 2022) - Chen, Taijun; Cao, Fei; Peng, Wenzhen; Wei, Ran; Xu, Qizhen; Feng, Bo; Wang, Jianxin; Weng, Jie; Wang, Min; Zhang, Xingdong
Highlights: It is the first time to propose and use endogenous lectin to repair critical size cartilage defect. It greatly enriches the content of tissue engineering. It may have great potential application prospect in cartilage tissue engineering. Abstract: Due to the lack of blood supply and nerve in articular cartilage, it is a great challenge to repair critical size cartilage defect, to maintain the phenotype of new chondrocytes and to restore joint function. We find that the endogenous cartilage extracellular matrix specific protein C-type lectin (CLECSF1) can be applied for the repair of cartilage defect. The endogenous expression of CLECSF1 can be achieved by integrating its coding gene into the recombinant lentiviral vectors. These vectors are used to transfect into bone marrow mesenchymal stem cells (BMSCs) and then these transfected BMSCs are seeded in a scaffold. We reveal that such scaffold can promote chondrogenic differentiation, enhance cartilage extracellular matrix deposition and maintain chondrocyte phenotype. Furthermore, such scaffold can repair critical size cartilage defect and finally achieve a full recovery of both structure and function. Therefore, we believe that such scaffold can be an ideal alternative strategy for the treatment of critical size cartilage defect in future.